Phosphoproteomics of cAMP signaling of Bordetella adenylate cyclase toxin in mouse dendritic cells. Issue 1 (December 2017) - Novák, Jakub; Fabrik, Ivo; Linhartová, Irena; Link, Marek; Černý, Ondřej; Stulík, Jiří; Šebo, Peter
Abstract The adenylate cyclase toxin (CyaA) of the whooping cough agentBordetella pertussis subverts immune functions of host myeloid cells expressing the αM β2 integrin (CD11b/CD18, CR3 or Mac-1). CyaA delivers into cytosol of cells an extremely catalytically active adenylyl cyclase enzyme, which disrupts the innate and adaptive immune functions of phagocytes through unregulated production of the key signaling molecule cAMP. We have used phosphoproteomics to analyze cAMP signaling of CyaA in murine bone marrow-derived dendritic cells. CyaA action resulted in alterations of phosphorylation state of a number of proteins that regulate actin cytoskeleton homeostasis, including Mena, Talin-1 and VASP. CyaA action repressed mTOR signaling through activation of mTORC1 inhibitors TSC2 and PRAS40 and altered phosphorylation of multiple chromatin remodelers, including the class II histone deacetylase HDAC5. CyaA toxin action further elicited inhibitory phosphorylation of SIK family kinases involved in modulation of immune response and provoked dephosphorylation of the transcriptional coactivator CRTC3, indicating that CyaA-promoted nuclear translocation of CRTC3 may account for CyaA-induced IL-10 production. These findings document the complexity of subversive physiological manipulation of myeloid phagocytes by the CyaA toxin, serving in immune evasion of the pertussis agent.